Flexible Average Inflation Targeting: How Much Is U.S. Monetary Policy Changing? - Coulter, Jarod; Duncan, Roberto; Martínez-García, Enrique (Pontificia Universidad Católica del Perú, 2022)
One major outcome of the Federal Reserve’s 2019–20 framework review was the adoption of a Flexible Average Inflation Targeting (FAIT) strategy in August 2020. Using synthetic control methods, we document that U.S. inflation rose post-FAIT considerably more than predicted had the strategy not changed (an average of 1.18 percentage points during 2020:M8–2022:M2). To explore the extent to which targeting average inflation delayed the Fed’s response and contributed to post-FAIT inflation, we adopt a version of the open-economy New Keynesian model in Martínez-García (2021) and document the economic consequences of adopting alternative measures of average inflation as policy objectives. We document three additional major findings using this general equilibrium setup: First, depending on how far back and how much weight is assigned to past inflation misses, the policy outcomes under FAIT are similar to those under the pre-FAIT regime. Secondly, we find that the implementation of FAIT can have large effects over short periods of time as it tends to delay action. However, over longer periods of time—such as the 1984:Q1–2019:Q4 pre-FAIT period—its effects wash out and appear negligible. Finally, we find that di˙erent average inflation measures explain an average of 0.5 percentage points per quarter of the post-FAIT inflation surge, indicating that targeting average inflation by itself can only explain part of the inflation spike since August 2020.
Keywords: Open-economy New Keynesian model; Monetary policy; Flexible average inflation targeting; Flexible inflation targeting; Survey; https://purl.org/pe-repo/ocde/ford#5.02.01